Srpski - Jevtić, Miloš (Serbian political thought, 2024)
Interpretations of the past inevitably involve the issue of losses experienced by a particular group. Because no particular discipline has a monopoly on understanding historical suffering, it is possible to examine it from different aspects. In this work, attention is focused on the relationship between suffering (as a fact) and victimhood, as a way of understanding the world. More precisely, this paper examines the representation of suffering maintained by group members, its consequences at the intergroup level (relations between countries and/or ethnic groups, relations between different groups within a society, etc.) and context on which empirical studies were concentrated. Moreover, the complex nature of collective victimhood is pointed out, as well as various socio-psychological factors related to this belief system. Finally, the implications of collective victimhood for current intergroup relations and guidelines for future research are discussed.